Reaction Kinetics of One-Pot Xylan Conversion to Xylitol via Precious Metal Catalyst - Hilpmann, Gerd; Kurzhals, Pascal; Reuter, Tom; Ayubi, Mick Miro (Frontiers in Chemical Engineering, 2020)
The hydrolytic hydrogenation of xylan to xylitol by a one-pot process was studied in detail in a batch reactor. The reaction was catalyzed by a combination of diluted sulfuric acid and precious metal Ru on carbon powder. Process parameters were varied between 120–150°C, while maintaining constant hydrogen pressure at 20 bar and an acid concentration equivalent to pH 2. The xylan solution consisted of 1 wt% beechwood powder (Carl Roth, >90%) in deionized water. Sulfuric acid was added to the solution until pH two was reached, then the 0.3 wt% catalyst powder (5% Ru on Act. C) was added and the solution was put into the batch reactor. The first approach of kinetic modeling began with conventional first-order kinetics and compared this to a more complex model based on Langmuir–Hinshelwood kinetics. The xylan and xylitol data reached a good fit. However, the modeling results also showed that the rate-limiting step of xylose-formation was still not represented in a satisfactory manner. Therefore, the model was adapted and developed further. The advanced model finally showed a good fit with the intermediate product xylose and the target product xylitol. The overall modeling methods and results are presented and discussed.